Peptide-Alkoxyamine Drugs: An Innovative Approach to Fight Schistosomiasis: “Digging Their Graves with Their Forks” - Ange W. Embo-Ibouanga; Michel Nguyen; Jean-Patrick Joly; Mathilde Coustets; Jean-Michel Augereau; Lucie Paloque; Nicolas Vanthuyne; Raphaël Bikanga; Anne Robert; Françoise Benoit-Vical; Gérard Audran; Philippe Mellet; et al. (Pathogens, 2024)
The expansion of drug resistant parasites sheds a serious concern on several neglected parasitic diseases. Our recent results on cancer led us to envision the use of peptide-alkoxyamines as a highly selective and efficient new drug against schistosome adult worms, the etiological agents of schistosomiasis. Indeed, the peptide tag of the hybrid compounds can be hydrolyzed by worm’s digestive enzymes to afford a highly labile alkoxyamine which homolyzes spontaneously and instantaneously into radicals—which are then used as a drug against Schistosome adult parasites. This approach is nicely summarized as digging their graves with their forks. Several hybrid peptide-alkoxyamines were prepared and clearly showed an activity: two of the tested compounds kill 50% of the parasites in two hours at a concentration of 100 µg/mL. Importantly, the peptide and alkoxyamine fragments that are unable to generate alkyl radicals display no activity. This strong evidence validates the proposed mechanism: a specific activation of the prodrugs by the parasite proteases leading to parasite death through in situ alkyl radical generation.